TINDAK PIDANA KORUPSI DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Azwandi; Muannif Ridwan (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2026)
Corruption is an extraordinary crime that has caused significant losses to the state and hindered the realization of good governance. This study aims to analyze corruption from the perspective of Islamic criminal law by examining the concepts of ghulul, risywah, and khianat, the application of criminal sanctions, and the effectiveness of the maqāṣid al-syarī'ah approach in preventing and combating corruption. The research employs a library research method by examining primary legal materials, including the Qur'an, Hadith, and legislation, as well as secondary legal materials in the form of books, scientific journals, and relevant scholarly literature. The collected data were analyzed using a descriptive qualitative approach. The findings indicate that corruption in Islamic criminal law constitutes a violation of the principles of trustworthiness (amanah), justice, and public welfare, and is substantively categorized as ghulul, risywah, and khianat. Since corruption is not classified as a ḥudūd or qiṣāṣ offense, sanctions are imposed through ta'zir, allowing judges to determine appropriate punishments based on the level of harm and public interest. Furthermore, the maqāṣid al-syarī'ah approach plays a strategic role in corruption eradication by safeguarding public wealth (hifẓ al-māl), strengthening moral integrity, and fostering accountability among public officials. Therefore, integrating Islamic criminal law values with the national legal system can contribute to a more comprehensive and effective anti-corruption framework.